Optimasi Desorpsi Kation Pb2+ dari Adsorben Silika Gel-GPTMS (Glycidoxypropyltrimethoxysilane) Termodifikasi Sulfonat dengan Metode Kolom - Auzakiyah, Sabella; Oktavia, Budhi; Sanjaya, Hary; Nizar, Umar Kalmar (Periodic, 2025)
Silica gel is a material that has two active sides, namely silanol (Si-OH) and siloxane (Si-O-Si) groups, but it is less effective as an adsorbent so it needs to be modified. Modification was carried out by adding sulfonate groups using GPTMS bridging compounds to improve the ability of silica gel to adsorb metal ions, such as Pb²⁺ cations. Characterization was performed using FTIR (Fourier Transform-Infrared) and XRF (X-Ray Fluorescence) to ensure the success of the modification process, while SSA (Atomic Absorption Spectrophotometry) was used to measure the effectiveness of the adsorption and desorption processes. In this study, adsorption and desorption were carried out using the column method. Adsorption of Pb²⁺ cation was carried out using silica gel-GPTMS sulfonate adsorbent at optimum conditions of 20 ppm concentration and pH 3. The process was followed by desorption to determine the optimum conditions, including the type of desorption agent (NaCl and CaCl₂), concentration, and flow rate. The results showed that the optimum conditions were obtained with CaCl₂ desorption agent, with a desorbed weight of 0.1707 mg and a desorption efficiency of 98.67%. The optimum concentration of CaCl₂ was 0.05 M with a desorbed weight of 0.1730 mg and a desorption efficiency of 100%. In addition, the optimum flow rate was 1 mL/min with a desorption percentage of 100%.